Os empoderados da agricultura familiar: capital social nos territórios do seridó e do sertão do Apodi/RN - Vieira, Denes Dantas (2013)
The study of social practices aims to overcome the theoretical dichotomies that insist on separating the individual from the social structures and vice versa. In this sense, the debate between objectivism and subjectivism in the construction of social reality still has occupied much time and reflection of various scholars of the humanities. Pierre Bourdieu has extensive work that seeks to advance in relation to the theoretical framework of traditional sociological explanations. Bourdieu`s approach regarding social practices is considered by some researchers as a synthesis of classical theories and by others as an attempt of complexify contemporary studies on the significance of social life. This thesis sharesthis effort to understand the social practices of agents, aiming to analyze the strategies of social and political leaders of family farming in the territories of Seridó and Apodi in Rio Grande do Norte, and it has as reference the theoretical and methodological concepts of habitus, field and capital, in Bourdieu. Therefore, we studied the trajectories of social leaders, here called agents as family farming in the two locations in Rio Grande do Norte. As techniques and procedures of the study, we resortedto semi-structured interviews, observations, participation in events and other researches. In conclusion, this thesis gives an account of the construction of two different relational fields for the activities of agents of family farming in the territories of Seridó and Apodi. Although the relational fields in the territories have been structured under the same prevailing institutions, which are: church, union and political party, the social practice of agents shows itself from social position and political variety. Even with the similarities and differences identified and analyzed in different fields of construction, the social relations of the agents in the territories result in the construction of gated communities, the social capital that is the substrate which the agents called empowered .